Pondering a Global BIPA: Politeness and Impoliteness in Verbal Interactions - Jumanto, Jumanto; Rahayu, Emik (State institute of islamic studies salatiga, 2020)
This opinionated research article is about politeness and impoliteness in verbal interactions within Indonesian interpersonal context. Accounts on politeness, camaraderie, distant language, close language, code-switching, and code-mixing are elaborated to come to the concept of impoliteness, i.e. rude situations and awkward situations. The interpersonal context here partly elaborates the types of hearer in the aspects of power and solidarity in Brown and Gilman’s theory (1968), the hearers of which are divided into superiors and close people in this article. Elements of both the Indonesian distant and close languages are presented, and how rude situations and awkward situations happen due to incompetence or ignorance of the two variants is illustrated. Illustrations of the Indonesian two variants and code-mixing of the two are given to highlight the rude and awkward situations. All this worldview on the teaching of Indonesian to non-native-speakers, i.e. pondering a global BIPA, should be regarded as efforts to develop as well as to market the Indonesian language to the global societies. Keywords Politeness, camaraderie, impoliteness, distant language, close language, rude situation, awkward situation, incompetence, code-switching, code-mixing, BIPA